Shattered justice - Furlong, Susan (Mystery writer) (Furlong, Susan (Mystery writer). Bone Gap travellers mystery, 2019)
"In the Appalachian town of Bone Gap, Tennessee, backwoods justice is more than just blind. It's swift, silent, and shockingly personal. Especially for Irish Traveller turned deputy sheriff Brynn Callahan... "Hear No Evil." The first message is found in a playground. A few feet away, a pair of human ears hang from the monkey bars. Deputy sheriff Brynn Callahan isn't sure what to make of this grisly scene. Do the ears belong to a murder victim? And if so, where is the body? One thing Brynn is sure of: the earring on one of the earlobes belongs to a man she met at a party the previous night... "Speak No Evil." The second message is discovered next to a human tongue on a park pavilion. Once again, no body is found. Brynn can't help but wonder if the crimes are rooted in the town's long-simmering tensions between Bone Gap locals and the barely tolerated Travellers who've settled there. "See No Evil." For Brynn, the investigation hits too close to home -- forcing her to confront the demons of her own past. But time is running out. Brynn has to track down the culprit before a third message is delivered -- and a third victim is claimed. Rich, atmospheric, and brilliantly chilling, Shattered Justice is the third Bone Gap Travellers novel from the [...] author of Splintered Silence and Fractured Truth." --